Studi Dan Analisa Arc Flash Dalam Menentukan Kategori PPE Di Gardu Induk Teluk Lembu PT. PLN Dengan Menggunakan Software ETAP 7.0.0 - Corry Komalasari; Nurhalim Nurhalim (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Arc Flash is dangerous happening in electric industry system. The cause of the damaged could be from a mistake of the system or maintenance procedur. Arc flash can broken tools and death of the workers around them. In order for our safety, we have to really take care of this system to avoid the damage and the life our workers. In this project, we will learn and make a research more and get throught it, we will learn about arc flash in Gardu Induk Teluk Lembu PT. PLN Pekanbaru. This study will teach us about how to count of arc flash with the standart of it an place the right category PPE.Keywords : arc flash, incident energy, PT. PLN, PPE, bus